Mathematical aspects of Wiener index - Knor, Martin (Ars mathematica contemporanea, 2016)
The Wiener index (i.e., the total distance or the transmission number), defined as the sum of distances between all unordered pairs of vertices in a graph, is one of the most popular molecular descriptors. In this article we summarize some results, conjectures and problems on this molecular descriptor, with emphasis on works we were involved in.
Keywords: chemical graph theory; kemijska teorija grafov; molecular descriptor; molekularni deskriptor; topological index; topološki indeks; total distance; totalna razdalja; Wiener index; Wienerjev indeks